The Effectiveness of Youtube on Elementary School Students’ Reading Skills During the Covid-19 Pandemic - Narwastu Ajeng Kurniasari; J. Priyanto Widodo; Shierly Novalita Yappi (Universitas Pahlawan Tuanku Tambusai, 2022)
The goal of this study was to examine how effective YouTube was as a learning medium during pandemic Covid-19 at SDN Bluru Kidul II Sidoarjo. The researchers used quantitative study, specifically the descriptive design, to assess the effect of YouTube as a learning tool used during pandemic Covid-19 on the reading skills of students at SDN Bluru Kidul II Sidoarjo in the academic year 2020/2021. Thirty students from class 6-A in the sixth grade were chosen as purposive samples, with 15 students serving as the experimental group and 15 serving as the control group. Test were given both before and after the treatment during this experiment. The results demonstrated that there are no statistically significant differences between the experimental and control groups in the pre-test, as the indicator level is (0.723), which is greater than 0.05 and statistically insignificant. Then, in the post-test, there are statistically significant differences between the experimental group and the control group, with the value of the indication level being (0.004), for mean scores of YouTube effectiveness in the experimental group with an average of 8.26 and 7.65 in the control group. The difference in mean scores between groups was statistically significant (t-value = 2.776, p-value =.004). According to the study's findings, the level of efficacy of using YouTube as a teaching tool to increase students' reading skills was extremely high.